Evaluation of a Varroa-resistant Apis mellifera selected stock under a commercial beekeeping system in Northern Argentina - Pietronave, Hernan Pablo; Russo, Romina Maria; Giacobino, Agostina; Palacio, María Alejandra; Liendo, María Clara; Lanzavecchia, Silvia Beatriz; Merke, Julieta; Scannapieco, Alejandra Carla (Taylor & Francis, 2025)
The selection and breeding of Apis mellifera colonies with a natural ability to survive Varroa destructor provide a long-term solution for a sustainable apiculture. In Argentina, a selected honey bee stock showing resistance to the mite (named R stock) has been identified and characterized under laboratory and field conditions. Currently, this selected material is being preserved for further evaluations in a commercial beekeeping system. In this study, we analyzed the population strength, mite levels and honey production of the R stock during two consecutive beekeeping seasons (a total of 16 surveyed apiaries). Results indicated low levels of adult bee mite infestation in R colonies from all apiaries (mean for both seasons: 0.3 ± 0.5% in spring; 1.5 ± 2.0% in summer). The colony strength and food stores of R colonies were similar between apiaries and seasons, and the honey yield per apiary ranged within the average production registered in commercial apiaries of the region. During each following autumn, a subgroup of R colonies was used to compare colony strength, food stores and mite infestation level with non-selected mite-susceptible colonies (named S stock). Overall, R colonies exhibited lower worker brood population, higher honey stores and lower levels of Varroa infestation in autumn compared to S colonies. Our results indicate that R stock displayed a significant potential to maintain the mite resistance phenotype under a commercial beekeeping system, better regulates its overwintering conditions, and exhibits a commercially adequate honey production. Present results provide tools for improving environment-friendly strategies to control varroosis in productive honey bee colonies.